School Leaders’ Preferences on School Location in Sierra Leone: An individual and school-level study - Espinoza-Revollo, Patricia; Ramirez, Ana; Atherton, Paul; Mackintosh, Alasdair (EdTech Hub, 2022)
Attracting qualified teachers to remote areas is a challenge in Sierra Leone. The pupil-to-qualified-teacher ratio in rural areas is 76:1, rising to 83:1 for schools located more than 15 km away from urban centres — well above the national target of 40:1. As equitable teacher deployment is crucial to ensure high-quality education, the Teaching Service Commission (TSC) aims to increase the deployment of qualified teachers to the most remote areas of the country. This paper describes a quantitative survey of school leaders’ perceptions of what shapes school location preferences and what factors need to be in place (i.e., incentives) to address the imbalanced distribution of qualified teachers in the country. We used data from a text message survey sent to school leaders around the country. This paper accompanies a qualitative inquiry on the same topic: What Matters Most for Teacher Deployment? A case study on teacher school choice preferences in Sierra Leone. Together with the qualitative study, our findings aim to address a gap in empirical evidence on teacher school preferences in Sierra Leone and contribute to a growing literature on teachers’ preferences in low- and middle-income countries. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6958056 10.53832/edtechhub.0106 2405685:MFH269TU
Keywords: _r:AddedByZotZen

Making strides to make digital literacy facilities accessible to children across Sierra Leone - Mason, Harriet (UNICEF Sierra Leone, 2022)
Making strides to make digital literacy facilities accessible to children across Sierra Leone
KerkoCite.ItemAlsoKnownAs: 2339240:YWVSPC2X 2405685:7WZT7QGS

Sierra Leone Education Sector Plan: Transforming learning for all 2022–2026 - Government of Sierra Leone (2022)
KerkoCite.ItemAlsoKnownAs: 2405685:8FE32XB4 2486141:8HN4J7TQ

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub; Education Commission; Fab Inc. (EdTech Hub, 2022)
ZenodoArchiveID: 5596875 ZenodoArchiveConcept: 5596874 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5896640 10.5281/zenodo.6504993 10.53832/edtechhub.0055 2405685:HT8ZGKAB 2405685:QAH4K4D6 2405685:SE5JPCX2
Keywords: HLR3; _r:AddedByZotZen

Using technology to improve the equity of teacher allocation in Sierra Leone: the challenge and a way forward - McBurnie, Chris; Vijil, Alejandra; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6497554 2339240:S7M2CQ4J 2405685:BRY3EXFT 2405685:KAZQRPA7
Keywords: _r:AddedByZotZen

What Matters Most for Teacher Deployment? A case study of teacher preferences in Sierra Leone - McBurnie, Chris; Godwin, Katie; Beoku-Betts, Iman; Bernard-Jones, Lydia; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6530321 10.53832/edtechhub.0095 2129771:G2ULWZXN 2339240:5JUXJ5N6 2339240:F43SL362 2405685:8GN4RWMR 2405685:L4RY53KI 2405685:Q8366KLT 2405685:XNBZSCS7 2486141:Z5CMZLCE
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

Using technology to support teacher continuous professional development in Sierra Leone - Beoku-Betts, Iman; Plaut, Daniel; Tanweer, Rabia; Tanweer, Daniel Plaut and Rabia, Iman Beoku-Betts (EdTech Hub, 2022)
In Sierra Leone, EdTech Hub has been working closely with the TSC and the World Bank over the last 18 months to design a TCPD model that will provide primary school teachers with tools to improve their literacy and numeracy instruction.

How Sierra Leone is betting on data to fight the impact of climate change on schools - Momoh, A; Atherton, Paul (Global Partnership for Education, 2022)
Data can significantly improve decision-making and allow for prioritizing interventions to benefit the most vulnerable populations. That’s why the ministry of Education in Sierra Leone is working with Fab Inc. to develop a web-based data tool that helps estimate and prioritize where new schools are really needed.
KerkoCite.ItemAlsoKnownAs: 2405685:AVDJP4T3 4042040:AJHHQGBH

‘Tich Mi Ar Tich Dem’: Designing a low-cost and scalable teacher professional development in Sierra Leone - Walker, Hannah; Tegha, Ghislaine; Lurvink, Anne-Fleur; McBurnie, Chris (Open Development & Education, 2022)
Reading Time: 4 minutes Over the past two decades, Sierra Leone has faced a series of shocks: a civil war, landslides, Ebola, and the COVID-19 pandemic. These shocks have aggravated the learning crisis that the country’s education system faces—and dramatically increased the pressure on teachers to deliver high-quality support to children. In this context, the Ministry of Basic and […]
KerkoCite.ItemAlsoKnownAs: 2339240:75HR9DSN 2405685:9TLXNWMJ 2405685:FBHX876D

2021 Annual School Census Final Report - Ministry of Basic and Senior Secondary Education, Sierra Leone (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:M7XYZTWF 2405685:C7C3BM9Z

Sierra Leone Education Sector Plan 2022-2026 - Ministry of Basic and Senior Secondary Education; Ministry of Technical & Higher Education (Government of Sierra Leone, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:JLYG52CA 2405685:MYV4GHKW

National Strategy for Out-of-School Children in Sierra Leone - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:F39I9PTD 2405685:BLKSJRLU

EMIS – MBSSE - Government of Sierra Leone (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:HKHF8XA6 2405685:BWCAJFI4 4656463:QV6UP6K3

Radical inclusion means teaching children in a language they understand - Bah, Chernor (Brookings, 2022)
Chenor Bah examines how Sierra Leone is trying to incorporate radical inclusion within the national education system by ensuring children are taught their mother-tongue for the first three to five years of schooling.
KerkoCite.ItemAlsoKnownAs: 2339240:FND65Y2H 2405685:7G5GS3YN

UNICEF Sierra Leone - UNICEF (2022)
Learn how we are supporting children across the country to reach their full potential.
KerkoCite.ItemAlsoKnownAs: 2339240:GFGZWUTT 2405685:LX8UD5MZ

EAGER Scenario Model – Sierra Leone - Cochran, Mikaela (The International Rescue Committee, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:CXF88QEI 2339240:UWF4RMSZ 2405685:UEIPLTJ9 2405685:UGYV6DSA

Individuals using the Internet (% of population) - Sierra Leone - International Telecommunication Union (World Bank Open Data, 2022)
Free and open access to global development data
KerkoCite.ItemAlsoKnownAs: 2339240:SAP2T6U2 2405685:EJFTAQ95

Sierra Leone Secondary Education Improvement Programme II (SSEIP II) - Foreign, Commonwealth Development Office (GOV.UK, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:KKMBX7JV 2405685:U74G9ACW

West African Senior School Certificate Examination: Sierra Leone Results Analysis - Ministry of Basic and Secondary Education (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:2WY3SC9N 2405685:YKA8Y8DM

Guidance Note on Education Data Mapping in Sub-Saharan Africa: Moving from theory to practice - Selwaness, Irene; Adam, Taskeen; Lawson, Laté; Heady, Lucy (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6339212 10.53832/edtechhub.0096 2339240:VJZWBP65 2405685:6JLQ7UC6 2405685:KQUDWCXC
Keywords: _r:AddedByZotZen

No Teacher is an Island: A case study on the enablers and barriers for effective school-based teacher professional development in Sierra Leone - Lurvink, Anne-Fleur; Bangura, Zainab; Fortune, Alhaji; George, Alex H.; Godwin, Katie; Mason-Sesay, Miriam; Moseray, David; Tholley, Ibrahim; Turay, Emmanuel B.; Haßler, Björn; Open Development & Education (OpenDevEd, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.0284 2405685:JDHJV2U4

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341501 ZenodoArchiveConcept: 7341500 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341501 10.53832/edtechhub.0138 2405685:E7C9MN3V
Keywords: _r:AddedByZotZen

Data Access and Protection Laws in Pakistan: A technical review - Halim, Waqas; Upadhyay, Arjun; Coflan, Caitlin (EdTech Hub, 2022)
The advancement of technologies has supported an exponential rise in the collection and use of data. Data, when used appropriately, can support better decision-making and inform innovation. Data has value to entrepreneurs and innovators who seek to design products that respond to user needs. However, the widespread collection and use of data have also spawned concerns about individual rights and data privacy. Issues related to collection, usage, dissemination, and access to data have also come to the forefront. To address these concerns, many countries across the globe have introduced data protection laws. This policy brief identifies and analyses global best practices in data protection and data access. It is developed in response to an inquiry related to data and research in the education sector, specifically in Pakistan. The brief explores the potential practical challenges in the enforcement and implementation of global good practices in the context of the data protection environment in Pakistan; it proposes a set of key recommendations for the Government of Pakistan, provincial governments, development partners, and other education-related ministries and public departments. Keywords: Data protection (laws), good practices, data access, privacy rights, children's data, sensitive data, data-driven policy, data integration, third-party data sharing, open data, data security, data governance, encryption An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6621244 10.53832/edtechhub.0098 2405685:GV4MKFZH
Keywords: _r:AddedByZotZen

Guidance on Pre-Assessment for Establishing E-Learning Centres - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5813529 10.53832/edtechhub.0084 2405685:DPWSAA9Z
Keywords: _r:AddedByZotZen

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341466 ZenodoArchiveConcept: 7341465 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341466 10.53832/edtechhub.0137 2405685:VVT2BI9M
Keywords: _r:AddedByZotZen

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5604677 10.5281/zenodo.5761966 10.53832/edtechhub.0069 2405685:CPP3A2WM 2405685:DM8N3E8E 2405685:PXUQJZTH
Keywords: Helpdesk Response; _r:AddedByZotZen

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2339240:LDWT8LYC 2405685:JPXVGB3A 2405685:MNMTIMGA 2405685:Q9J54HFA
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

National Policy on Radical Inclusion in Schools Implementation Plan 2021-2026 - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:ZIUJRRAJ 2405685:J2YDQU25

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0115 2339240:3KZX9ARU 2405685:BBQE9QUM 2405685:UUDK52LQ 2405685:YB52PCMQ
Keywords: ⛔ No INSPIRE recid found

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5721401 10.53832/edtechhub.0070 2339240:CHJR9D5G 2339240:RFJZSHMG 2405685:FE3VBQQW 2405685:NFXKD34I 2405685:PU8D6GXN 2405685:SY9TIAMH
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 4: Content curation - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fourth of five reports on the development of a proof of concept for the Hub and describes our observations during content curation. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803092 10.53832/edtechhub.0078 2405685:9VKXVKGI
Keywords: _r:AddedByZotZen

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5849102 10.53832/edtechhub.0071 2339240:5YT7LKSS 2405685:6FN5VTP7 2405685:8UMQILZ9 2405685:GMA7II34 2405685:WEG87IDU
Keywords: _r:AddedByZotZen